1996
DOI: 10.1128/jb.178.23.6913-6920.1996
|View full text |Cite
|
Sign up to set email alerts
|

Properties of the FhuA channel in the Escherichia coli outer membrane after deletion of FhuA portions within and outside the predicted gating loop

Abstract: Escherichia coli transports Fe3؉ as a ferrichrome complex through the outer membrane in an energydependent process mediated by the FhuA protein. A FhuA deletion derivative lacking residues 322 to 355 (FhuA ⌬322-355) forms a permanently open channel through which ferrichrome diffused. This finding led to the concept that the FhuA protein forms a closed channel that is opened by input of energy derived from the electrochemical potential across the cytoplasmic membrane, mediated by the Ton system. In this study, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
48
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(54 citation statements)
references
References 36 publications
6
48
0
Order By: Relevance
“…These results suggest a level of plasticity along the length of this well-conserved protein that allows TbpA to accommodate insertions with relatively little impact on structure or function. Results from a limited deletion analysis of TbpA (5) are in agreement with this assertion, and both studies support the theory that gonococcal TbpA, like other TonB-dependent receptors (3,7,33,34,39,44,47) is resilient to various types of mutations.…”
Section: Discussionsupporting
confidence: 74%
“…These results suggest a level of plasticity along the length of this well-conserved protein that allows TbpA to accommodate insertions with relatively little impact on structure or function. Results from a limited deletion analysis of TbpA (5) are in agreement with this assertion, and both studies support the theory that gonococcal TbpA, like other TonB-dependent receptors (3,7,33,34,39,44,47) is resilient to various types of mutations.…”
Section: Discussionsupporting
confidence: 74%
“…This is presumably reflective of a fundamental structural difference between the two barrels; the TolC barrel is mainly engaged in the removal of hydrophobic inhibitors from the cells, while the porin barrel lets small hydrophilic molecules diffuse through it. The conversion of FhuA and FepA, which are substrate-specific and TonB-dependent OMP transporters, to general diffusion OMPs has also been reported (17,31). These transporters do not allow general solute diffusion because of the existence of a large plug domain that blocks the inside of the barrels (4, 10).…”
Section: Discussionmentioning
confidence: 99%
“…These transporters do not allow general solute diffusion because of the existence of a large plug domain that blocks the inside of the barrels (4, 10). However, deletions that shorten the plug domain do allow the nonspecific diffusion of a variety of compounds, including novobiocin and rifampin (17,31).…”
Section: Discussionmentioning
confidence: 99%
“…Uptake of microcin J25 and infection of Salmonella serovar Typhimurium by phage ES18 may require both the cork and the ␤-barrel. We have previously shown that the prominent loop of the FhuA ␤-barrel (18), which is loop 4 in the E. coli FhuA crystal structure (7,20) and lies above the cell surface, serves as the principal binding site of the phages and colicin M (13,14,15). This result implies that TonB, without the help of the cork, can change the conformation of loop 4 such that binding of phages T1 and 80 triggers DNA release from the phage head.…”
Section: Discussionmentioning
confidence: 99%